2012
DOI: 10.5923/j.ms.20120205.10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Zn, Cu, Pb and Cd in the Tissues and Organs of <i>Psetta </i><i>M</i><i>axi</i><i>ma</i> from Sinop Coasts of the Black Sea, Turkey

Abstract: In the present study, turbot Psetta maxima were selected and analyzed for the Zn, Cu, Pb and Cd concentrations in the muscles, livers and gonads. The results revealed that Zn concentrations were the highest followed by Cu; Pb and Cd being the lo west in the tissues (muscle) and organs (gonads and liver). The liver metal concentrations showed the highest values, whereas the muscle concentrations were the lowest. A co mparison between the concentration of each metal found in males and females found significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Recently, Bat [22] reviewed the results of the selected heavy metals (Fe, Zn, Ni, Cu, Mn, Pb, Cd and Co) in fish captured from the Black Sea coasts of Turkey and the metal concentrations decrease in the order Zn>Fe>Cu> Mn>Pb>Ni>Co>Cd. Below is a summary of the general distribution of the eight heavy metals in the tissues and organs: In general, results of the present study show a trend similar to what many authors have pointed out before around the world, about the accumulation of these metals in fish tissues [7,10,[23][24][25][26][27][28][29]. Also, authors agree that liver is the highest concentrations of heavy metals analysed are shown.…”
Section: Resultssupporting
confidence: 88%
“…Recently, Bat [22] reviewed the results of the selected heavy metals (Fe, Zn, Ni, Cu, Mn, Pb, Cd and Co) in fish captured from the Black Sea coasts of Turkey and the metal concentrations decrease in the order Zn>Fe>Cu> Mn>Pb>Ni>Co>Cd. Below is a summary of the general distribution of the eight heavy metals in the tissues and organs: In general, results of the present study show a trend similar to what many authors have pointed out before around the world, about the accumulation of these metals in fish tissues [7,10,[23][24][25][26][27][28][29]. Also, authors agree that liver is the highest concentrations of heavy metals analysed are shown.…”
Section: Resultssupporting
confidence: 88%
“…Data that were related to heavy metal concentration in turbot muscle and liver tissues, as reported in Europe (including Turkish Black Sea coast), were collected from the scientific literature [ 72 , 73 , 74 , 75 , 76 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Figure 2 presents the sampling area reported in the scientific sources used for developing the analytical framework.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, FishBase ( ) considers Scophthalmus maeoticus (Pallas, 1814) as a synonym of Scophthalmus maximus (Linnaeus, 1758). Therefore, all three names that appear in the scientific literature used in present study, Scophthalmus maeoticus [ 106 ], Psetta maxima maeotica [ 72 , 75 , 76 , 100 , 101 , 102 , 107 , 109 ], and Scophthalmus maximus [ 73 , 74 , 99 , 103 , 108 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metal levels in liver and in digestive system tract tissues or organs offish are also higher than those in edible muscles at significant levels. Many studies argued that liver is the main detoxification destiny and one of the most important metal storage organs by the digestive tract (Agusa et al, 2007;Farkas et al, 2002;Jaffar et al, 1988;Khaled, 2004;Krishna Kumar et al, 1990;Sobhanardakani et al, 2011;Sofia, 2005;Turkmen et al, 2009;Yousuf & Ahmed, 2010;Bat et al, 2012). It should be kept in mind that the most metals especially non-essentials stored in the liver and kidney depends on the intensity of exposure time and state of renal excretory function.…”
Section: Overall Conclusionmentioning
confidence: 99%